Tiefenzeit. Anton Bruckner als Gegenstand der energetischen Musikbetrachtung - Hoffmann, Tim Martin (Schweizer Jahrbuch für Musikwissenschaft, 2026)
This paper attempts to establish and develop the concept of deep time in historical musicology. The idea of deep time, primarily mapped by Stephen Jay Gould, refers to the geological discovery of earth’s history in the late 18th and early 19th centuries, and considers its far-reaching implications for the relativization and dynamization of human concepts of time. Recent general historical research has also shown the significance of the idea for the establishment of modern historical consciousness and concepts of structural history. A musicological exploration of the idea has not yet materialized, however, proves to be a desideratum, particularly regarding 19th century music. Based on a general foundation of the concept of musical deep time, this paper demonstrates the pre-conceptual presence of deep time thinking in the Bruckner monographs of August Halm and Ernst Kurth. With a view to both formal theory under the sign of geological metaphors and structural-historical considerations, Bruckner proves to be an exponent of musical deep time from the perspective of music theory and aesthetics as well as music historiography.